Understanding and managing emotions: The basis for children to develop strong character and attain academic excellence / Zakiah Mohd Noordin and Associate Prof. Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
A child's emotional health plays a significant role in developing their moral character and achieving academic brilliance. The Faculty of Pharmacy, UiTM has conducted a program titled "Emotion Management: Impact on Character and Academic Excellence" at Sekolah Puncak Alam 2 on September 26, 2023 as a preventative measure to help young students build their character and improve their academic performance. The event, which included 20 faculty members as committee members and facilitators, attracted 430 standard six students in the morning session and 500 standard one students in the afternoon. The Faculty of Pharmacy at UiTM has initiated this program to help students better understand and control their emotions, with the hope that these abilities will help them develop social and emotional competence. A counselor from the counseling unit of the UiTM Selangor Branch gave a presentation to introduce the idea of emotions at the start of the program. This was a crucial step towards comprehending one's own thoughts and feelings. In this session, participants learned how to recognize and control their emotions in order to develop a solid moral character and prosper in their academic endeavors. The counselor next discussed how to handle stressful situations and unpleasant feelings. Children's life is affected by this issue, especially those in the standard 6 who will soon be going to the secondary school. They learned crucial skills for fostering positive interactions with their classmates as well as basic but efficient relaxing methods. The use of media and technology in today's world has a big impact on kids' lives. Additionally, the program also addressed how media and technology affect children's emotions. Students learned how to manage and use media sensibly as well as how to deal with its unfavorable impacts.